Gender Segregation In Education In Multicultural Communities - Hadi Nurcahyono, Okta (Opción, 2019)
A Single-Sex Education (SSE) policy is a form of gender segregative education that is applied in several countries in the world, including Indonesia. Like the implementation of Single-Sex Education (SSE) education, the majority of which are applied in Muslim countries, in Indonesia, especially in Surakar- ta, the application of the Single-Sex Education (SSE) policy occurs in private schools or in Islamic foundations. The application of gender segregative ed- ucation is an effort to translate norms or values from the teachings of Islam that recognize the concept of “mahram”. Differing from research with similar themes, this research is sociological in nature with an ethnomethodological research approach. This research studies the construction of reality made by the subject in the process of daily interaction of students who are subject to Single-Sex Education (SSE). Restrictions on interaction with the opposite sex results in changes in the pattern of interaction with students. As in Erving Goffman’s theory, there are two models of interaction carried out by students, namely the existence of a “front stage”, namely the world of social students when they are in school and the backstage is the social relations of students in society or social media. Students abiding by regulations are bound not to communicate with the opposite sex who is not a “mahram” when at school (front stage). But with this gender segregation there is created a new arena in the “backstage” they are hidden in secret interaction with the opposite sex, which can be through social media, or by meeting in person at a retail store. Gender segregative education is a challenge in its own right, especially in a multicultural society.